The relationship of workplace spirituality, job characteristics employee engagement, and employee wellbeing - Sudar Rheina Romadhoni; Tatik Suryani (Enrichment : Journal of Management, 2023)
Due to the decreasing of shariah financial business performance, wellbeing of employees come a big problem during pandemic. How to improve wellbeing from psychological perspective, especially from employee engagement, spirituality at work and job characteristics are important to be researched. The purpose of this research is to examine and analyze the effect of workplace spirituality and job characteristics on employee engagement and their impact on the wellbeing of millennial employees in Islamic financial institutions. This research is applied research by survey design. Questionnaire was used for collecting data and distributed by Google Form. Data was analyzed by Partial Least Square. The results of this study indicate that workplace spirituality and job characteristics have a positive effect on employee engagement, and employee engagement has significant influence towards employee wellbeing